Congenital proximal radioulnar synostosis - Dogra, B. B.; Singh, Manmohan; Malik, Anil (Indian Journal of Plastic Surgery, 2003)
Congenital proximal radio-ulnar synostosis is a rare anomaly and is often part of syndromes such as Crouzon, Apert's and Poland's. We have successfully managed one such case with bilateral involvement not associated with any other congenital deformity. He has been managed by performing derotation osteotomy through the synostosis mass with gratifying results.
Keywords: Congenital; Radio-ulnar synostosis